Opportunities for Organizing Distance Learning Presented by the Moodle Platform: Experience in the Conditions of the COVID-19 Pandemic - Vladimirovna Grigoryeva, Natalia (2021)
The implementation of modern information technologies in education presents a promising direction of the pedagogical science since it makes it possible to prove educational services through a specialized information educational environment – a combination of information resources, technical devices, and telecommunication channels enabling the exchange of educational information at a distance. The goal of the present study is to analyze and identify the opportunities of the Moodle platform in education as a whole and in studying English at a university in particular. The methodological basis of the study is formed by the analysis of the experience of teachers of the Department of English Language, the methods of teaching English, and a survey of experts in the area. Using the Moodle platform in the process of teaching future English teachers allows both teachers and students to easily exchange files, carry out personal communication, and receive feedback. The presented electronic course allows teachers to create their own e-learning courses in foreign languages.